Effect of impurities on the Raman scattering of 6H-SiC crystals - Lin,Shenghuang (2012)
Raman spectroscopy was applied to different-impurities-doped 6H-SiC crystals. It had been found that the first-order Raman spectra of N-, Al- and B-doped 6H-SiC were shifted to higher frequency when comparing with undoped samples. However, the first-order Raman spectra of V-doped sample was shifted to lower frequency, revealing that there existed low free carrier concentration, which might be induced by the deep energy level effect of V impurity. Meanwhile, the second-order Raman spectra are independent of polytype and impurity type.